Uma sistematização da obra filosófica de Álvaro Vieira Pinto - Barcat, Iuri Michelan (2024)
This work consists of an investigation about the thought of the Brazilian philosopher Álvaro Vieira Pinto. It is a systematical exposition (always interpretative) oriented by the systematic reconstitution of the essential of Álvaro Vieira Pinto’s thought. Our investigation is situated in the context of the works written by the author, chronologically, from the booklet Ideology and National Development (1956) onwards, including later texts that we have available today. We present the thesis that throughout these works, a systematic and unitary philosophical thought unfolds, but whose synthetic exposition must be produced, and this is what our work consists of. As a result, we want, precisely, from the systematic interpretation of his texts, to expose the foundations of this philosophical conception and present how his thought is structured and developed internally. There is no work by the author that is dedicated exclusively and specifically to the systematization we undertake here, which collects elements left over from all the author’s works investigated by us, and that’s why this thesis may shed new light on the set of problems involving the author and his work. The fact that the Brazilian thinker has written about a great variety of themes, such as Work, Nation, Science, Technology, Cybernetics, Education, Politics etc., seems to demand some kind of interpretation that allows us its adequate unification, especially since this has always been an explicit goal of Vieira Pinto himself, that is, that his thought could be the representation of the totality of his object. This thesis seeks to provide this interpretation.